2021
DOI: 10.1101/2021.02.23.21252268
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The emergence and ongoing convergent evolution of the N501Y lineages coincides with a major global shift in the SARS-CoV-2 selective landscape

Abstract: The emergence and rapid rise in prevalence of three independent SARS-CoV-2 '501Y lineages', B.1.1.7, B.1.351 and P.1, in the last three months of 2020 has prompted renewed concerns about the evolutionarily capacity of SARS-CoV-2 to adapt to both rising population immunity and public health interventions such as vaccines and social distancing. Viruses giving rise to the different 501Y lineages have, presumably under intense natural selection following a shift in host environment, independently acquired multiple… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
90
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(106 citation statements)
references
References 96 publications
9
90
0
Order By: Relevance
“…The onset date of VOI N.9 here estimated around mid-August roughly coincides with the estimated timing of emergence of the VOI P.2 in late-July 6 and shortly precede the detection of a major global shift in the SARS-CoV-2 fitness landscape after October 2020 [20]. These findings indicate that 484K variants probably arose simultaneously in the two most prevalent viral lineages circulating in Brazil around July-August, but may have only acquired some fitness advantages, which accelerated its dissemination, after October 2020.…”
Section: Discussionsupporting
confidence: 72%
“…The onset date of VOI N.9 here estimated around mid-August roughly coincides with the estimated timing of emergence of the VOI P.2 in late-July 6 and shortly precede the detection of a major global shift in the SARS-CoV-2 fitness landscape after October 2020 [20]. These findings indicate that 484K variants probably arose simultaneously in the two most prevalent viral lineages circulating in Brazil around July-August, but may have only acquired some fitness advantages, which accelerated its dissemination, after October 2020.…”
Section: Discussionsupporting
confidence: 72%
“…The copyright holder for this preprint this version posted March 25, 2021. ; https://doi.org/10.1101/2021.03.21.21253418 doi: medRxiv preprint Convergent mutations seem to play an essential role in the evolutionary dynamics of SARS-CoV-2. Intense selective pressure from the immune system against prolonged infections may promote intrahost variants with higher adaptive value [12,[35][36][37][38][39]. Previous studies have shown that both N501Y and E484K have independently emerged in patients with persistent infection [35,40].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, additional fourplex master mixtures contained sets of primers and probes to determine whether a SARS-CoV-2 isolate belongs to the L or S strain (Tang et al 2020). Other examples of fourplex reactions included primer-probe sets to identify the SNP found in Spike gene at position 23,063 (thymine instead of adenine) that results in an amino acid substitution N501Y that triggers a stronger interaction of the Spike receptor-binding domain with the human cell-surface receptor angiotensinconverting enzyme 2 (ACE2) (Leung et al 2021;Martin et al 2021). This multiplex approach could facilitate tracking of SARS-CoV-2 variants that carry mutations.…”
Section: Limits Of Detection (Lod)mentioning
confidence: 99%
“…Since the beginning of the COVID-19 pandemic, several studies have reported genomic sequence variations of SARS-CoV-2 isolates (Leung et al 2021;Martin et al 2021;Rondinone et al 2021;Tegally et al 2021a;Tegally et al 2021b). Among these genetic variations, a single nucleotide polymorphism (SNP) found at position 8,782 (in orf1ab; C instead of T) of SARS-CoV-2 genomic sequence is a hallmark of the L strain (Tang et al 2020), whereas the unaltered nucleotide is found at the same position in the S strain.…”
Section: Introductionmentioning
confidence: 99%